Enhancing properties of iron and manganese ores as oxygen carriers for chemical looping processes by dry impregnation. (1st February 2016) - Haider, S.K.; Azimi, G.; Duan, L.; Anthony, E.J.; Patchigolla, K.; Oakey, J.E.; Leion, H.; Mattisson, T.; Lyngfelt, A.
Highlights: Oxygen carriers were produced by impregnation of metal ores with iron and manganese oxides. The oxygen carriers were examined in a bench scale fluidised-bed reactor for CLOU and gaseous fuel conversion. Impregnation of these ores positively influences their mechanical properties. Above 850 °C, iron ore based oxygen carriers exhibited full syngas conversion. Iron ore impregnated with Mn2 O3 showed significant CLOU behaviour. Abstract: The use of naturally occurring ores as oxygen carriers in CLC processes is attractive because of their relative abundance and low cost. Unfortunately, they typically exhibit lower reactivity and lack the mechanical robustness required, when compared to synthetically produced carriers. Impregnation is a suitable method for enhancing both the reactivity and durability of natural ores when used as oxygen carriers for CLC systems. This investigation uses impregnation to improve the chemical and mechanical properties of a Brazilian manganese ore and a Canadian iron ore. The manganese ore was impregnated with Fe2 O3 and the iron ore was impregnated with Mn2 O3 with the goal of forming a combined Fe/Mn oxygen carrier. The impregnated ore's physical characteristics were assessed by SEM, BET and XRD analysis. Measurements of the attrition resistance and crushing strength were used to investigate the mechanical robustness of the oxygen carriers. The impregnated ore's mechanical and physical properties were clearly enhanced by the impregnation method, with boosts in crushing strength of 11–26% and attrition resistance of 37–31% for the impregnated iron and manganese ores, respectively. Both the unmodified and impregnated ore's reactivity, for the conversion of gaseous fuel (CH4 and syngas) and gaseous oxygen release (CLOU potential) were investigated using a bench-scale quartz fluidised-bed reactor. The impregnated iron ore exhibited a greater degree of syngas conversion compared to the other samples examined. Iron ore based oxygen carrier's syngas conversion increases with the number of oxidation and reduction cycles performed. The impregnated iron ore exhibited gaseous oxygen release over extended periods in an inert atmosphere and remained at a constant 0.2% O2 concentration by volume at the end of this inert period. This oxygen release would help ensure the efficient use of solid fuels. The impregnated iron ore's reactivity for CH4 conversion was similar to the reactivity of its unmodified counterpart. The unmodified manganese ore converted CH4 to the greatest extent of all the samples tested here, while the impregnated manganese ore exhibited a decrease in reactivity with respect to syngas and CH4 conversion.